Thermal, Spectral and Magnetic Studies on Fluorenone Thiosemicarbazone Complexes of Cobalt(II) and Nickel(II) - Laly, S.; Parameswaran, Geetha (Asian Journal of Chemistry, 2010)
Fluorenone thiosemicarbazone (FTSC) forms 1 : 2 complexes with cobalt(II) and nickel(II). Both of these complexes are found to be non electrolytes in nitrobenzene and dimethyl formamide. Square planar structures are assigned for the complexes based upon spectral and magnetic measurements. IR studies reveal that these complexes are formed by the replacement of the hydrogen atom of the SH group by metal ion with N and S coordinating to the metal. On the basis of thermal studies, the relative thermal stabilities of the chelates can be given as [CoL2] > [NiL2].